2022
DOI: 10.3390/atmos13010138
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Effects of Land Surface Characteristics on Planetary Boundary Layer Parameters for a Modeled Landfalling Tropical Cyclone

Abstract: This study examined whether varying moisture availability and roughness length for the land surface under a simulated Tropical Cyclone (TC) could affect its production of precipitation. The TC moved over the heterogeneous land surface of the southeastern U.S. in the control simulation, while the other simulations featured homogeneous land surfaces that were wet rough, wet smooth, dry rough, and dry smooth. Results suggest that the near-surface atmosphere was modified by the changes to the land surface, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
5
1
Order By: Relevance
“…DRYX also simulated more accumulation farther right of the TC tracks and simulated less accumulation in the inner core region closer to the TC (Figure 9e). This result in the drier experiment is notably different from the result in Wang and Matyas (2022), which found lower rain rates within the TC inner core in the moister land surface experiments [25].…”
Section: Precipitationcontrasting
confidence: 99%
See 1 more Smart Citation
“…DRYX also simulated more accumulation farther right of the TC tracks and simulated less accumulation in the inner core region closer to the TC (Figure 9e). This result in the drier experiment is notably different from the result in Wang and Matyas (2022), which found lower rain rates within the TC inner core in the moister land surface experiments [25].…”
Section: Precipitationcontrasting
confidence: 99%
“…Numerical simulations have suggested that drier land surface conditions can reduce rainfall amounts by 20% [20]. Additionally, simulations of TCs moving over a moister land surface produce lower rain rates in the inner core of TCs [25]. To date, less research has been done to understand how the land surface can impact the atmospheric stability surrounding a TC and, hence, the TC rainfall pattern, particularly in the distant rainband region.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the precipitation intensity nuclei ranged from 30 to 35 mm·hr −1 over a wide area of Santa Catarina at the time of landfalling, but it notable decreased in intensity and spatial extent when Catarina moved inland. The evaporation rate decreases when a TC moves over land as a response to the increase of the roughness length and, therefore, the moisture availability (Wang and Matyas, 2022). Vianna et al .…”
Section: Resultsmentioning
confidence: 99%
“…This would advect more moisture from land into the TC system as the TC approaches the coast (Figure 4). A similar precipitation peak before landfall is observed in a previous study of Fani (Zhao et al ., 2020) and in TCs landfalling in Florida (Wang and Matyas, 2022). The peak is observed after the landfall in the case of PRecycled$$ {P}_{\mathrm{Recycled}} $$ (dotted line).…”
Section: Resultsmentioning
confidence: 99%
“…To track the land‐originating ET, the land in the domain for the entire simulation period (including the lag) is considered the source region to calculate PRecycled$$ {P}_{\mathrm{Recycled}} $$. This lead of 10 days in the simulation, referred to as lead time from hereon, could affect the forecasting accuracy of the WRF model (Wang and Matyas, 2022). However, such a setup would help us account for all the atmospheric ET originating from land and understand its contribution to a TC from its origin.…”
Section: Methodsmentioning
confidence: 99%